Scenes from the civilizational effects of the tribe of Rabi`ah al-Hijazi on the tribes of al-Baja through the writings of Taqi al-Din al-Maqrizi (d. 845 AH /1441 CE) - ghendouz, aicha; Chapani, noure ddine (The Algerian Historical Journal, 2026)
This research aims to shed light on one of the topics that fall within the Hijazi migrations to East Africa, which has always been dealt with briefly with a focused study on a type of historical writings, and I thought that my contribution would be in dealing with the historical relations between the tribes of Rabia and Beja through historical textes of the historian "Taqi al-Din al-Maqrizi", I focused mainly on the degree of political influence, which was primarily represented in changing the method of bequeathing power to the islamic way, and thus the Rabia community became loyal and obedient by the beja tribe. Then stand on the factor of social affinities between the two tribes that led indirectly to the spread of Islam among them. And the research paper aimed to aproximate a more realistic picture of the Arab character and customs that spread in the Beja community, and at the same time sought to emphasize the effectiveness of the civilizational influence for this tribe, which was represented in the emergence of human reconstruction and the flourishing of commercial activity, the community of Beja.